Penguatan Potensi Usaha Mikro, Kecil dan Menengah (UMKM) Berbasis Bisnis Digital di Desa Mekarharja Ciamis - Agung, Ahmad; Mubarrok, Dede Husni; Timorani, Jihandika Nurul; Fittriani, Seassy; Komara, Bayu; Puteri, Fauziah Rifna (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
This community service article aims to analyse the impact of digital business implementation on strengthening the potential of MSMEs in Mekarharja Village, Purwaharja Subdistrict, Banjar City, West Java. MSMEs not only create jobs and drive local economic growth, but also support social inclusion and provide new opportunities for MSMEs to access global markets through e-commerce. This research uses a descriptive research method with a qualitative approach. The research data collection techniques were carried out through observation, interviews and document review studies to support the research. the findings of this service confirm that the implementation of digital-based businesses provides a solid foundation for promoting the growth and strengthening of MSMEs in today's sophisticated era. the findings of this service confirm that the implementation of digital-based businesses provides a solid foundation for promoting the growth and strengthening of MSMEs in today's sophisticated era.